Physical Culture is an Integral Part of Human Cultural Development - Olimjonovich, Murodov Nozimjon (Research Parks Publishers, 2021)
This article provides a comprehensive analysis of the concept of physical culture. It is based on the importance of physical education in human life. The role of physical culture in the healthy development of children, leading a healthy lifestyle is explained.